Serotonin signals through a gut-liver axis to regulate hepatic steatosis - Wonsuk Choi (Nature Portfolio, 2018)
No effective pharmacological treatments exist for nonalcoholic fatty liver disease (NAFLD). Here, the authors show that serotonin concentration in the portal blood is increased in nine human subjects and in mice fed a high-fat diet, and that local serotonin signaling ablation, either genetically or with an antagonist, prevents hepatic steatosis in mice.